Pengaruh Working Capital Turn Over Ratio Dan Current Ratio Terhadap Profitabilitas (Studi Kasus Pada PT. Gudang Garam Tbk Di Bursa Efek Periode 2011 – 2018) - Minsyah Fuadi; Ahmadi Aidi (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
The purpose of the research is to examine the influence of Working Capital Turn Over Ratio and Current Ratio on Profitability by using a measure of Return In Investment. Sampling from this study was taken from the financial statements of PT. Gudang Garam Tbk in the 2011-2018 period from the Indonesia Stock Exchange and data processed using the SPSS version 24 programs.The results of this study indicate that Working Capital Turn Over Ratio has a positive and significant effect on Return In Investments based on the results of the t test obtained Working Capital Turn Over Ratio has a tcount of 6.240 greater than the value of t-table which is 2.051. While the Current Ratio has a negative and opposite effect on the Return In Investment, with a t-count of -3,395 greater than the value of t-table that is 2,051. As the simultaneous Working Capital Turn Over and Current Ratio has an effect on Return In Investments with a significant 0,000 smaller than alpha (α) = 0.05.